PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuliyanti, Gita; Surya Fauzia Pertami , Yuli; Taofik Ismail, Muhammad; Damardjati Ruseka, Fahmi (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2025)
This study aims to analyze and test the influence of Enterprise Risk Management disclosure on company value. Using purposive sampling techniques, ninety-one manufacturing companies listed on the Indonesia Stock Exchange (2019-2021) were selected as samples in this study. We used panel data regression to test the effect of Enterprise Risk Management disclosures on Company value. The results of the study show that the disclosure of Enterprise Risk Management has a positive and significant effect on the Company's value by 36.88%.